Formation of 1-octen-3-ol from Aspergillus flavus conidia is accelerated after disruption of cells independently of Ppo oxygenases, and is not a main cause of inhibition of germination - Miyamoto,Kana; Murakami,Tomoko; Kakumyan,Pattana; Keller,Nancy P.; Matsui,Kenji (PeerJ, 2014)
Eight-carbon (C8) volatiles, such as 1-octen-3-ol, are ubiquitous among fungi. They are the volatiles critical for aroma and flavor of fungi, and assumed to be signals controlling germination of several fungi. In this study, we found that intact Aspergillus flavus conidia scarcely synthesized C8 volatiles but repeated freeze-thaw treatment that made the cell membrane permeable promoted (R)-1-octen-3-ol formation. Loss or down regulation of any one of five fatty acid oxygenases (PpoA, PpoB, PpoC, PpoD or lipoxygenase) hypothesized contribute to 1-octen-3-ol formation had little impact on production of this volatile. This suggested that none of the oxygenases were directly involved in the formation of 1-octen-3-ol or that compensatory pathways exist in the fungus. Germination of the conidia was markedly inhibited at high density (1.0 × 109spores mL−1). It has been postulated that 1-octen-3-ol is an autoinhibitor suppressing conidia germination at high density. 1-Octen-3-ol at concentration of no less than 10 mM was needed to suppress the germination while the concentration of 1-octen-3-ol in the suspension at 1.0 × 109 mL−1 was under the detection limit (<1 µM). Thus, 1-octen-3-ol was not the principal component responsible for inhibition of germination. Instead, it was evident that the other heat-labile factor(s) suppressed conidial germination.
Keywords: Aspergillus flavus; Conidia; Carbon-eight volatiles; 1-Octen-3-ol; Fatty acid oxygenases; Germination; Spore